Associations of Fat Mass and Fat Distribution With Bone Mineral Density in Non-Obese Postmenopausal Chinese Women Over 60 Years Old - Fan, Jingzheng; Jiang, Yuyan; Qiang, Junlian; Han, Bin; Zhang, Qiang (Frontiers in Endocrinology, 2022)
Background: Loss of bone mineral density (BMD) is one of the most significant complications of menopause. Fat mass (FM) is closely related to BMD. However, the associations of FM and fat distribution (FD) with BMD in postmenopausal women remain elusive. This study aimed to determine the associations of body fat accumulation and FD with BMD in non-obese postmenopausal elderly women. Methods: This cross-sectional study enrolled 357 healthy postmenopausal elderly women (aged 60.2 to 86.7 years). Total lean mass (LM), total FM, body fat percentage (BF%), android and gynoid fat, and total and regional BMD were measured by dual-energy X-ray absorptiometry (DXA). FD was assessed by the android-to-gynoid fat ratio (AOI). The body composition associations between FM, LM, AOI, and BMD of each skeletal site were performed with the Pearson’s correlation test and multiple regression analysis. Results: In univariate analyses, both FM and LM were positively associated with total and regional BMD (all P<0.01), while the relationships between AOI and BMD were not significant in any skeletal sites except for the head. In multivariate linear regression models controlling age, years since menopause, and height, FM continued to show a positive effect when analyzed independently (standard β ranged from 0.141 to 0.343, P<0.01). When also adjusting for LM, the associations between FM and BMD did not change (standard β ranged from 0.132 to 0.258, P<0.01), while AOI harmed BMD at most skeletal sites (total body, hip, femoral neck, arm, leg, and head) (standard β ranged from −0.093 to −0.232, P<0.05). The results remained unchanged when replacing FM with BF% (standard β ranged from −0.100 to −0.232, P <0.05). Conclusions: In this sample of non-obese postmenopausal elderly Chinese women, total FM had a significant positive relationship with BMD. AOI was inversely associated with BMD, suggesting that for postmenopausal women, being properly weight gain but controlling central obesity may have beneficial effects on bone health.